2014
DOI: 10.1021/jp509068s
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Gas Sensing by Indium Oxide: An Operando Spectroscopic Raman-FTIR Study

Abstract: The ethanol gas-sensing mechanism of indium oxide has been investigated in detail by Raman spectroscopy in combination with resistance measurements of the indium oxide sensor material and Fourier transform infrared (FTIR) gas-phase analysis. The observed surface species depend on the gas environment and sensor temperature. Raman spectra taken at lower operating temperatures of the sensor (190°C) during ethanol gas sensing reveal the presence of surface acetate and reduced indium oxide. Addition of oxygen to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 28 publications
2
40
0
10
Order By: Relevance
“…Previous operando Raman studies on undoped In2O3 gas sensors have shown that during ethanol (EtOH) gas sensing the sensor signal can be directly correlated with the nature of the adsorbates, the presence of surface hydroxyl groups and the indium oxide oxidation state [2,3] Turning now to recent results on Ag doped In2O3, Figure 1 shows operando Raman spectra recorded after switching from air to 250 ppm EtOH/air at 190 °C. At higher wavenumbers, the disappearance of hydroxyl groups at 3639 and 3656 cm −1 (O-H stretch) is accompanied by the formation of acetate based on the bands at 871 cm −1 (C-C stretch) and 2935 cm −1 (C-H stretch) [3]. Interestingly, upon exposure to 250 ppm EtOH/air, the low wavenumber region shows dramatic changes, which are reversible and which can be related to the change in the Ag state during EtOH sensing.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous operando Raman studies on undoped In2O3 gas sensors have shown that during ethanol (EtOH) gas sensing the sensor signal can be directly correlated with the nature of the adsorbates, the presence of surface hydroxyl groups and the indium oxide oxidation state [2,3] Turning now to recent results on Ag doped In2O3, Figure 1 shows operando Raman spectra recorded after switching from air to 250 ppm EtOH/air at 190 °C. At higher wavenumbers, the disappearance of hydroxyl groups at 3639 and 3656 cm −1 (O-H stretch) is accompanied by the formation of acetate based on the bands at 871 cm −1 (C-C stretch) and 2935 cm −1 (C-H stretch) [3]. Interestingly, upon exposure to 250 ppm EtOH/air, the low wavenumber region shows dramatic changes, which are reversible and which can be related to the change in the Ag state during EtOH sensing.…”
Section: Resultsmentioning
confidence: 95%
“…Understanding the mode of operation of metal-oxide gas sensors (e.g., SnO2, In2O3) is of great scientific and economic interest. Such a knowledge based approach requires the development and application of spectroscopic tools to monitor the relevant surface and bulk processes under working conditions (operando approach) [1,2] In previous studies on In2O3 sensors, we applied combined operando Raman/gas-phase FT-IR spectroscopy to ethanol gas sensing [2,3] In this contribution, we will present recent results on ethanol and CO detection using undoped and Ag doped In2O3 gas sensors, demonstrating the advantages of (i) operando Surface Enhanced Raman Spectroscopy (SERS) to monitor the metal oxidation state, and (ii) extending the operando Raman/FT-IR setup by UV-Vis spectroscopy to reveal the degree of In2O3 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…These 3D hierarchical nanostructures are assumed to be the most effective because of their porous nanostructures formed by the adjacent building blocks. On the other hand, gas sensing performances of SnO 2 can remarkably be improved once the size shrinks to a critical value of 14 nm (2 λD) [9,10]. This is confirmed by Yamazoe et al [11], claiming that the critical size of SnO 2 nanomaterials is 5-15 nm for the effective detection of H 2 and CO.…”
Section: Introductionmentioning
confidence: 80%
“…The temperature gap has a strong impact on the semiconducting properties and the surface chemistry of the gas sensing material, as the ionization of defects [ 23 , 24 ], adsorption of molecules [ 25 , 26 ] or chemical reactions [ 27 , 28 ] strongly depend on temperature. Heating the sample to typical operation temperatures between 200 and 400 °C is possibly restricted by the spectroscopic technique as such, e.g., requiring ultralow temperatures or by low pressures, which my trigger unwanted changes in the sample due to heating in the absence of oxygen.…”
Section: In-situ and Operando Methodologymentioning
confidence: 99%
“…The electronic structures can be probed by UV/vis Diffuse Reflectance Spectroscopy (DRS) [ 35 , 36 ], XAS and X-ray emission spectroscopies (XES) [ 34 , 37 , 38 ]. The surface chemistry is mainly investigated by Diffuse Reflectance Infrared Fourier-Transform Spectroscopy (DRIFTS) [ 28 , 39 , 40 , 41 ] and Raman spectroscopy [ 27 , 42 ]. An overview of operando methods for SMOX gas sensors is given in Figure 1 [ 14 ].…”
Section: In-situ and Operando Methodologymentioning
confidence: 99%